The Nature and Extent of Job Separations in Germany: Some New Evidence from SOEP - Getinet Haile (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This paper analyses job separations in Germany using data from the German Socio- Economic Panel spanning from 1984 to 2003. Based on detailed reasons for job separation and different SOEP samples, the paper attempts to establish the nature of job separations in Germany. It brings to light some patterns of separations that have hitherto been unexplored. The findings of the study suggest, among others, that minority group status is important in characterising job separations, particularly in the event of exogenous shocks. Targeting minorities in the face of a major shock of the sort experienced in Germany might be a policy option.
Keywords: J6; J15; C35; 330; job separations; job turnover; economics of minorities